Features of the Kazakh and Chinese arts and crafts. (Journal of Oriental Studies, 2016)
This article analyzes the developmental functions of arts and crafts of the Kazakh and Chinese peoples as an integral aesthetic, cultural, historical and socio-pedagogical phenomenon in terms of pedagogical practice. National forms, artgraphic methods, cultural and historical traditions, realities, customs of two nations are reviewed.
Keywords: arts and crafts; jade; national painting; jewelry; psychological aspect; customs and traditions